ENHANCING THE EFFICIENCY OF ENVIRONMENTAL AND ECONOMIC RISKS MANAGEMENT FOR OIL AND GAS PRODUCING ENTERPRISES IN AZERBAIJAN - Suleymanov, Gazanfar Salman; Turkan, Sheydai Ali (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
Apsheron region is the main oil producing region of Azerbaijan. One of the main problems that have risen here since the beginning of the exploitation of oil fields is the contamination of landscapes with oil and oil products. At present, a significant part of the land is heavily polluted with oil and formation water, the hydrological regime of the territory has deteriorated, and the soil structure has been destroyed. The State Oil Company of the Azerbaijan Republic (SOCAR) is taking decisive steps in improving environmental safety management systems in accordance with international requirements, as well as in solving existing environmental problems, protecting public health and the rational use of natural resources. Prevention of pollution as a result of onshore oil and gas operations, elimination of the consequences of pollution is a priority task of SOCAR's environmental policy. The analysis of the current state of environmental and economic risk management at SOCAR showed that, despite all the positive changes in the field of reducing environmental pollution, the company still needs to enhance the effectiveness of measures to manage these risks. In particular, despite the successful implementation of a number of measures to reduce air pollution, the amount of air emissions from stationary sources at the company's enterprises remains significant. A number of extremely important, environmentally oriented initiatives does not sufficiently cover the oil and gas production by onshore enterprises and are mainly focused on offshore enterprises, which are being developed independently and jointly with foreign companies. In order to enhance the effectiveness of risk management, it is proposed a departure from a centralized, at the company level, form of management and the formation of a risk management system (RMS) directly at the enterprises themselves. To implement this approach, some changes in the organizational structure of enterprises are recommended, including the creation of a department for managing all risks to which the enterprise may be exposed. The creation of such a department directly in Oil and Gas Production Asset will allow more efficient use of the potential and real capabilities of the enterprise in the face of uncertainty and associated risks, the necessary optimization of the directions and methods of risk management, which are reflected in the risk minimization program, developed with the aim of ensuring the sustainable development of the enterprise.